Cerebral amyloid angiopathy distribution in older people: A cautionary note - Vafa Alakbarzade; Jonathan MR French; David R Howlett; Johannes Attems; Paul T Francis; Sarah Stratton; Camilla N Clark; Anthony C Pereira; Atticus H Hainsworth (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2021)
Abstract Introduction Radiolabeled ligands for fibrillar amyloid beta (Aβ) peptides are used in positron emission tomography (PET) for dementia diagnosis. Current ligands do not discriminate parenchymal amyloid plaques from cerebral amyloid angiopathy (CAA). Methods We undertook neuropathological examination of 65 older people (81.6 ± 7.96 (mean ± SD) years, 27F/38M): 15 with neuropathological diagnosis of AD, 25 with neuropathological diagnosis of other neurodegenerative dementias (Lewy body dementia and Parkinson disease dementia), and 25 without significant neurodegenerative pathology. Results We observed CAA in non‐Alzheimer's dementia (non‐AD dementia) and control brains, of comparable extent to those with neuropathologically confirmed AD. Aβ‐positive vessel density did not differ significantly between non‐AD dementia and control groups. Across all subjects there was a highly significant correlation between vessel Aβ40 density and vessel Aβ42 density (Spearman rho = 0.855, P < .001). CAA was absent or sparse in subcortical white matter across all patient groups. Conclusion Our data indicate that CAA can be abundant in non‐AD brains and raise a cautionary note regarding interpretation of amyloid PET imaging.